Influence of iron deficiency anemia on the formation of systemic immunity in children - Banadyha, Nataliya (Journal of Education, Health and Sport, 2016)
Banadyha N. V. Influence of iron deficiency anemia on the formation of systemic immunity in children. Journal of Education, Health and Sport. 2016;6(1):93-100. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44646 http://ojs.ukw.edu.pl/index.php/johs/article/view/44646 http://pbn.nauka.gov.pl/works/692678 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.12.2015. Revised 25.12.2015. Accepted: 09.01.2016. INFLUENCE OF IRON DEFICIENCY ANEMIA ON THE FORMATION OF SYSTEMIC IMMUNITY IN CHILDREN N. V. Banadyha SHEI “Ternopil State Medical University by I.Ya.Horbachevsky, Ministry of Health of Ukraine”, Ternopil, Ukraine Abstract Purpose: to evaluate the functional status of the immune system in children of various age with diagnosed iron deficiency anemia. Patients and methods. The study involved 106 children under the age of 3 years with diagnosed iron deficiency anemia (IDA). Were analyzed thoroughly factors of development of sideropenic conditions and probable immunodeficient disease. Activity of systemic immune response development in children with anemia was monitored by indexes of cellular (T-, B-lymphocytes) and humoral immunity (Ig A, M, G). Results. In young children with IDA was founded significant reduction in the total number of T- lymphocytes (CD3+), CD22+, CD16+, CD4+ and CD8+, compared with values of the control group, both as in the case of presence of an infectious inflammatory disease, and in the case of its absence. Also was diagnosed decreasing of absolute and relative amount of T- lymphocytes and their subpopulations, and that indicated to some extent of reduction of both helper and suppressor activity of cellular immunity. Analyzis of immunoglobulins values in the serum of patients with IDA without any concomitant acute infectious disease showed specific dysimmunoglobulinaemia, which was associated with significantly low levels of IgG, IgA, and normal values of Ig M. However, in the case of IDA, combined with acute respiratory disease, was tracked significant increasing in Ig A and Ig M values, with decreased level of IgG. Significant difference between level of immunoglobulin A (p <0.05) and M with the same indexes of the group of children without any acute disease indicates for the activation of the humoral response while presence of infectious pathology. Conclusions. In young children with IDA was founded significant reduction in the total number of T- lymphocytes and their subpopulations, and that indicated reduction of both helper and suppressor immunity activity, and can serve as proof of the violation in rates of physiological maturation and differentiation of the immune response. The last one is indicated by significant deficit of Ig G in children with IDA, which shows late immune start in patients with anemia, regardless of existing of some infectious disease or without it. Key words: iron deficient anemia, infants, toddlers, immunity, children.